Distribusi dan kelimpahan parasitoid telur, Telenomus spp. di sumatera barat: status dan potensinya sebagai agens pengendali hayati - Eddy Susiawan; Netti Yuliarti (Perhimpunan Entomologi Indonesia, 2006)
Exploration of egg parasitoids was conducted by collecting host eggs from soybean, vegetable crops, peas, corn and rice fields in West Sumatra. We found six species Telenomus distributed throughout studied locations in West Sumatera. Four species have been identified, namely T. remus Nix., T. rowani Gah., T. dignus Gah., T. dignoides Nix., whereas two others have not been identified yet because there is no appropriate identification key. The results showed that the both T. rowani Gah. and T. dignus Gah were distributed in all studied locations with different individual number, but they could be potentially be used as biocontrol agents in the future. The highest numbers of species was found in Tanah Datar and Solok with different abundance, whereas the lowest number of species were in Agam and Lima Puluh Kota.